POLITICAL COMMUNICATION OF ACEH GOVERNOR’S CANDIDATE IN INDONESIAN LOCAL LEADERS’ ELECTION IN 2017 - A.G Hamdani (IAIN Salatiga, 2019)
This study aims to examine the political communication of the Aceh governors’ candidate during the Indonesian local leaders’ election in 2017. The focus of the study is to analyze the political communication of the candidates and the effectiveness of the campaign. This study used a qualitative approach. The findings show that both candidates used propaganda political communication, communication techniques, and various political campaign strategies. The political propaganda strategy and campaign the governor candidate of Irwandi-Nova were far more intense, effective, widespread and comprehensive in quality and quantity compare to Muzakkir-TA. Although the candidate of Irwandi-Nova cannot predict their supporters for granted, apparently their political communication strategy, propaganda and political approach have effectively anesthetized Acehnese voters and placed them as the winner of the Aceh Governor's Election that counted for 898,710 votes while Muzakkir-TA only gained 766,427 votes.